Content validity of the Post-Stroke Guidance and Follow-up Booklet - Bruna Fonseca Vasconcelos; Douglas de Araújo Vilhena; Luísa Fonseca Vasconcelos; Paula Mariana Munno Guimarães Corrêa; Magnania Cristiane Pereira da Costa; Juliana Nunes Santos; Thaís Peixoto Gaiad Machado (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to provide sources of content validity evidence for the Post-Stroke Guidance and Follow-up Booklet. Methods: a quantitative-qualitative approach, using two Delphi method and content analysis rounds. The Educational Content Validation Instrument in Health was sent to 53 independent judges. A Content Validity Index above 0.90 was considered. Results: of the 14 nurses who participated, 64.3% have experience with stroke care, 35.7% with primary care and 64.3% with educational material production. In content analysis, judges' suggestions were stratified into four categories: material conformation, objectivity, accuracy and perception. Spelling changes were made to the images, addition of functionality scale, adequacy of technical terms and language. The Content Validity Index in the second round showed a concordance of 0.97. Conclusions: the booklet presented satisfactory content validity sources of evidence.